2002
DOI: 10.2136/sssaj2002.3700
|View full text |Cite
|
Sign up to set email alerts
|

Leachate Collection Efficiency of Zero‐tension Pan and Passive Capillary Fiberglass Wick Lysimeters

Abstract: Lysimeter leachate collection efficiencies (LCEs), which are the measured leachate volume divided by estimated percolation water, are needed to convert measured leachate volumes to actual leachate fluxes. In this study, LCE of zero‐tension pan and passive capillary fiberglass wick lysimeters were evaluated and directly compared. A total of 18 pan and 18 wick lysimeters were installed 1.2 m below the soil surface in tilled and no‐till plots. From May 1995 to April 2000 the lysimeter LCEs were evaluated using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 17 publications
2
49
0
Order By: Relevance
“…Zhu, Fox, and Toth (2002) indicated that PPL for this study site ranged from 22 to 25% (for nine lysimeters) under NT for 4 of 5 years. During a much wetter year observed during this previous study, annual PPL was about 50%.…”
Section: Water Drainagementioning
confidence: 84%
See 4 more Smart Citations
“…Zhu, Fox, and Toth (2002) indicated that PPL for this study site ranged from 22 to 25% (for nine lysimeters) under NT for 4 of 5 years. During a much wetter year observed during this previous study, annual PPL was about 50%.…”
Section: Water Drainagementioning
confidence: 84%
“…A detailed description of pan lysimeter construction and installation was provided by Jemison and Fox (1992), and for the wick lysimeter by Zhu, Fox, and Toth (2002). A brief description is provided here.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations